Analisis Budaya Sekolah Dalam Pembentukan Karakter di Pondok Pesantren MA Nurul Muhajirin Sukatani Kec. Tanjung Lago Banyuasin - Romli, Romli; Ibrahim, Ibrahim (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2021)
Character education is the education of values, morals, and character aimed at shaping students’ abilities to realize goodness in their daily lives. The current reality of education indicates a character crisis influenced by the dominant emphasis on cognitive aspects; therefore, formal educational institutions need to strengthen school culture as a strategy for character formation. This study aims to analyze school culture in shaping students’ character. This research is a field study employing a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. Data analysis used an interactive model consisting of data reduction, data display, and data verification. The results of the study indicate that school culture consists of academic culture and social culture. Academic culture includes a reading culture, a learning culture, and a creativity culture. A reading culture shapes religious character, responsibility, independence, and curiosity. A learning culture fosters responsibility, independence, and curiosity, while a creativity culture develops responsibility, independence, social care, and curiosity. Social culture includes a culture of mutual respect, the 3S culture (smile, greeting, and salutation), and a culture of simple living. A culture of mutual respect forms social care and responsibility. The 3S culture shapes religious character, social care, and responsibility. Meanwhile, a culture of simple living develops independence, responsibility, and social care. Thus, strengthening school culture plays an important role in the holistic development of students’ character.